THE IMPACT OF POVERTY ON THE PRACTICE OF VOTE BUYING IN NIGERIA: A FOCUS ON THE 2015 AND 2019 GENERAL ELECTIONS - Nandes Dickson, Cinjel; Onu Salihu, David; Danjuma, Joseph (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
Vote buying involves the process whereby either or both the political party or a candidate of a political parties strive to buy vote of an electorate in an approaching or an imminent election. It is more of an isolated practice which tends to disseminate corruption in a political system. This act has taken the centre stage in the economic and political process of most countries in the region. Poverty in these nations and Nigeria precisely kept reawaking despite several reforms and policies in the country. Poverty to a larger extent had impacted negatively on the growth of the incidence of vote buying in the country. A lot of voters have indulged into the act and this is due to the continual spread of poverty in the country. Vote pricing, buying and selling in Nigerian often takes place in two forms. These menace mostly manifested in the form of elite’s compensation and the practice of spreading monetary worth during campaign and electioneering period. Monetary worth and materials such as the use of money, food additive, grains, shoes, attires, salt, maggi, sugar, wrappers, exercise books and many others are mostly used as the bait to entice the desperately awaiting voters. The study generated data from array of both published and unpublished materials such as text books, journal papers, newspapers, magazines, reports of panel of investigation and commission of inquiry, internet materials, seminar and conference papers among many others. The main instrument used to generate data was interview. In interpreting our data, the relationship between poverty and vote buying was established at both theoretical and empirical level. Empirically, we used a qualitative and historical method that was critical and analytical in providing descriptive and historical details. This was further complemented by descriptive analysis. It was established that poverty had negatively impacted on the spread and commonness of vote buying in Nigeria. Recommendations such as: establishment of practicable law to curb the act, agrarian reforms, introduction of economic and developmental programmes, functional voter’s education and many others were proffered.